ANALYSIS OF THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND PHYSICAL FITNESS LEVEL - April, Dwi Aprilianto; Ariesna, Rachmat Dody (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the relationship between nutritional status and physical fitness level of class X students at SMK Satu Nusa 2. The study used a correlational quantitative approach with data collection techniques through tests and direct measurements. The results of the Shapiro-Wilk normality test showed that the nutritional status and physical fitness data were normally distributed. The regression linearity test (ANOVA) shows that the relationship between the two is linear. Pearson correlation analysis found a very strong and significant negative relationship between nutritional status and physical fitness level. This means that the higher the nutritional status of students (especially those categorized as obese), the lower their physical fitness level. This finding emphasizes the importance of maintaining a balanced nutritional status to improve the quality of physical fitness in school-age adolescents. This study is expected to serve as a basis for designing appropriate nutrition and exercise programs in the school environment.